كميات الأمطار وأهميتها في تنمية الموارد المائية دراسة تطبيقية في المنطقة الساحلية خلال الفترة (2002-2012) - طيوب, محمود; الحداد, خلدون (Latakia University Journal - Economic and Legal Sciences Series, 2014)
نظراً لارتفاع معدل هطول الأمطار في المنطقة الساحلية، وقلة المشاريع المائية فيها مقارنةً مع العرض المائي، وبالتالي عدم الاستفادة من مياه الأمطار بدرجة كبيرة. رأينا أن نلفت الانتباه إلى أهمية الاستفادة من كميات الأمطار في تنمية الموارد المائية في المنطقة الساحلية, وذلك من خلال ايجاد نموذج رياضي يربط بين كميات الأمطار وبين الطلب (السكاني والزراعي والصناعي) على الموارد المائية خلال الفترة (2000-2012), وذلك بهدف إمكانية التنبؤ فيها مستقبلاً, وبما يكفل حسن إدارتها وترشيد استخدامها في القطاعات المختلفة. وكان من أهم نتائج البحث: 1- تتطور كميات الأمطار بشكل متناقص خلال الفترة (2002-2012), وبمعدل سنوي بلغ (1.84%). 2- يتطور حجم الطلب على الموارد المائية بشكل متزايد خلال الفترة (2002-2012), وبمعدل سنوي بلغ (3.41%) للطلب السكاني, و(3.47%) للطلب الزراعي, و(6.25%) للطلب الصناعي. 3- هناك فائض بين كمية الموارد المائية المتاحة وحجم الطلب عليها, حيث يتناقص هذا الفائض خلال الفترة (2002-2012) بمعدل سنوي بلغ (2.97%). 4- إن تقدير الفائض بين كمية المتاح من الموارد المائية, وحجم الطلب عليها سيتناقص في العام 2023 عما سيكون عليه في العام 2013 بمعدل سنوي (-3.23%). Because rainfall in the coastal area is high and water projects are nearly missing, we think it is important to make use of available water resources. In order to predict future rainfalls and suggest proper management of resources, we created a mathematical model linking rainfall amounts between demand (population, agricultural and industrial) on water resources during the period (2000-2012). Results show the following: Rainfalls decreased during the period ( 2002-2012) at an annual rate of (1.84%). Demand on water resources increased during the period (2002-2012) at an annual rate of (3.41%) of the population demand, and (3.47 %) of the agricultural demand, and 6.25% for industrial demand. There is a surplus of available water resources and the size of demand for them, with the surplus decreasing during the period (2002-2012) at an annual rate (2.97 %). The estimation of the surplus between the amount of available water resources and the size of the demand for them will decrease in 2023 from what it was like in the year 2013 at an annual rate (-3.23%).